J. Noel Kilgour interviewed by Hazel de Berg in the Hazel de Berg collection - Kilgour, J. Noel (Jack Noel), 1900-1987.; De Berg, Hazel, 1913-1984. (1965)
Kilgour speaks of his life during the first World War years; his studies; his stay in England and subsequent return to Australia; his association with Dobell; his main interest in art; mediums used; his paintings; teaching art.
Also available online
Transcript available (10 p.)
Keywords: Kilgour, J. Noel -- 1900-1987 -- Interviews; Artists as teachers -- Australia -- Interviews; Painters -- Australia -- Interviews